Relasi Antara Politik Identitas Terhadap Proteksi Perdagangan dibawah Pemerintahan Donald Trump - Setiawan, M. Chairil Akbar; Ginting, Garcia Krisnando Nathanael; Ilmar, Anwar (Journal of Political Issues, 2020)
This article seeks to explain the change in US foreign policy in the economy under Donald Trump's administration since 2017. The analysis will be based on the relationship between Identity Politics and Protectionist policies pursued by Trump. Trump's economic policy orientation shows a significant shift compared to some previous governments. The author will use a Qualitative method with the Explanatory analysis model. Protectionism approach becomes Trump's main platform, which is manifested in rejection of the framework of cooperation in the Trans Pacific Partnership (TPP), renegotiation of economic agreements with Canada and Mexico,or the recent tension of having Trade War against China since 2018. Nationalism sentiment, vigilance on the part of foreigners, or the reification of the identity of the United States are considered to be the main elements that have caused Trump to turn away from the global regime of Neoliberalism. The author wants to examine the relationship between Identity Politics and Trump's economic-political platform. The rise of Identity Politics is not a main cause toward Protectionism in the United States. Trump merely harnessed the failure of neoliberal policies from previous administrations by using the rhetoric of nationalism and identity politic.